Epidemic encephalitis. sleeping sickness - Gonzáles Olaechea, Max (1920)
In late 1915 and during 1916. He called their attention to RENE CRUCHET and other French doctors some patients whose predominant brain symptoms, but their comments were incomplete due to the incessant movement of the military hospitals in the areas of war; only in April 1917 CRUCHET, MOUTlER and CALMETTES founded observations in 40 cases under the name catalogaro encef allo-myelitis, published a statement in the Bulletin de la Societe Medicale des hospitaux Paris. Later in March 1918 drew attention NETTER appearance in the Paris region of epidemic disease, which by its clinical characters resembled that observed in 1917 in Austria by VON ECONOMO and other practical, calling lethargic encephalitis. During 1918 and 1919 new cases have been identified in England, France, Italy and other nations in Europe, Australia, USA. UU. and other cities in South America. Between us, in the month of August 1919 Dr. MONET exhibited at the National Academy of Medicine observing a case of sleeping sickness he attended; Dr. ODRIOZOLA reported at the same meeting an observation made in the service of "Dos de Mayo" hospital and finally Dr. JULIAN ARCE has published an interesting work in connection with the observation of otherwise perfectly studied by him.